The effects of compensation and benefits, working environment, and training and career development on professional commitment among employees in private dental clinics - Thanh, Le Trung; Anh, Do Hoang Van; Trung, Le Quang; Anh, Luong Tuan (Edelweiss Applied Science and Technology, 2026)
This study investigates the determinants of professional commitment among employees in private dental clinics. Drawing on Herzberg’s two-factor theory and social exchange theory, the study examines the effects of compensation and benefits, working environment, and training and career development. Data collected from 305 employees were analyzed using reliability testing, EFA, and regression analysis. The results indicate that compensation and benefits have the strongest positive impact on professional commitment, followed by training and career development, while the working environment shows no significant effect. These findings highlight the importance of financial incentives and human capital investment in enhancing employee commitment in healthcare settings. The study contributes to the literature by providing empirical evidence from an emerging economy context. Managerial implications emphasize the need for competitive compensation, continuous training, and digital transformation in human resource management. Limitations and future research directions are also discussed.